Off-label use of orphan medicinal products: a Belgian qualitative study. Issue 1 (December 2016) - Dooms, Marc; Cassiman, David; Simoens, Steven
Abstract Background Off-label use of (orphan) medicinal products for (rare) diseases is quite common but not underpinned by clinical studies to confirm efficacy and safety. No risk-analyses by regulatory agencies are carried out. The objective of this study was to map off-label use of orphan medicinal products in Belgium in terms of attitude towards off-label prescribing, factors influencing off-label prescribing, disclosure of information towards the patient, reporting of off-label use, risks and consequences. Most of the EMA authorized orphan drugs are fully reimbursed in Belgium under well-defined circumstances. Moreover, a "Special Solidarity Fund" takes care of some specific cases eventually prescribed off-label. Methods Semi-structured interviews with seven physicians with expertise in the treatment with and six experts in the reimbursement of orphan medicinal products in Belgium. This task was performed by five last-year pharmacy students after having studied profoundly the medical literature around off-label prescribing. They had no previous contact with the participants. Results Most participants do agree with the off-label use if the medicinal product is quite safe and well-tolerated, if the on-label indication is rather general and when all other options have failed in some specific, evidence-based indications, especially in children. Before starting off-label use, the patient/family needs to be fully and clearly informed. The treatment is not reimbursed but sometimes sponsored by the company or by charity funds. Reporting of the outcome is necessary to avoid losing valuable information. The prescriber is responsible and can be held accountable. Conclusions While there is support from physicians and reimbursement experts, there is also concern in case of off-label use, mainly for reasons of patient safety especially when medicinal products are prescribed off-label in the absence of medical or scientific justification and driven by cost-containment motives.